Assessing the impact of uncontrolled landfills on the environment in Fez: a DPSIR analysis - Boukhlouf, Yasmine; Benabdelhadi, Mohammed; Kassou, Omar (Euro-Mediterranean journal for environmental integration, 2025)
The research assesses the environmental impacts of waste management in Fez, Morocco, in line with the legal standards set by law 28–00 on waste management and law 12–03 on environmental impact assessment. Using the DPSIR framework (Drivers, Pressures, State, Impact, Response), 43 unregulated landfills were analyzed to assess their impacts on water, air, soil, biodiversity, and socio-economic activities. The results reveal medium to major impacts, predominantly local but continuous, affecting soil, water, air, and ecosystems. Human-related impacts include noise pollution and health risks, though there are also positive effects, such as job creation. While drought has lessened some water-related impacts, the overall disruption to ecosystems and communities is significant. The key message of this investigation is that unregulated waste management in Fez is causing ongoing environmental damage, particularly through illegal landfills. This research underscores the necessity of improving waste management strategies by integrating systematic evaluation methods like DPSIR. By providing a more systematic approach to understanding the complex interactions between waste and the environment, these findings are essential for shaping future waste management policies and promoting better environmental integration in urban planning.